Harnessing Beneficial Microbes for Abiotic Stress Tolerance and Nutrient Uptake in Horticultural Crops: Mechanisms, Applications, and Future Prospects - Subedi, Puja; Pandey Chhetri, Abishek; Atreya, Padma Nath (Nepalese Horticulture, 2025)
Abiotic stresses, including drought, salinity, and nutrient limitations, pose significant threats to horticultural productivity and soil integrity. Beneficial microorganisms-such as arbuscular mycorrhizal fungi , plant growth-promoting rhizobacteria , and endophytes-provide sustainable solutions by enhancing plant stress tolerance, nutrient acquisition, and soil health. This review critically examines the mechanisms by which these microbes alleviate stress, highlighting their roles in hormonal regulation, antioxidant defense, osmotic balance, and modulation of gene expression. Particular attention is given to microbial consortia, which often outperform single-strain inoculants under complex, multi-stress environments. Grapevine is employed as a representative model to illustrate species-specific microbial interactions. Additionally, recent innovations in microbial delivery including drip fertigation and portable bioreactors are evaluated for their potential to translate laboratory insights into field-level applications. By synthesizing advances across microbial taxa and delivery technologies, this review emphasizes the transformative potential of microbiome-based strategies for sustainable and climate-resilient horticultural systems.